Assessing University Contributions to Sustainability in Europe: A Data-Driven Analysis of SDG 12 (Responsible Consumption) and SDG 13 (Climate Action) - Lena Malešević Perović; Maja Mihaljević Kosor; Nikša Alfirević (World)
With intensifying demands for sustainability in higher education—particularly tied to the United Nations’ Sustainable Development Goals (SDGs)—universities remain central to fostering responsible consumption and climate action. However, a significant gap persists in quantifying how effectively higher education institutions (HEIs) contribute to SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action). The extant literature has largely relied on qualitative evidence or limited case studies, lacking comprehensive, data-driven comparisons across nations. This study addresses the existing gap in the literature by applying data envelopment analysis (DEA) to assess how efficiently European universities bolster sustainable consumption and climate initiatives. Drawing on secondary data from the 2023 Times Higher Education (THE) Impact Rankings and the Sustainable Development Report, this method provides new insights on how HEIs coordinate with their countries’ broader sustainability objectives. Our results show differences in efficiency among universities across 24 European countries, shaped by unique national contexts and policies. The study results can be used by university administrators and policymakers, who aim to improve the university contributions to achieving UN SDGs.